Risk Management Analysis in Snake Fruit Supply Chain through House of Risk Approaches (Case study in CV “MT”) - Fitriandini, Dinar; Roessali, Wiludjeng; Wulandari, Suci (Agro Bali : Agricultural Journal, 2024)
Snake fruit is a native Indonesian fruit that has become one of the leading export horticultural commodities. However, the distribution process of snake fruit exports to foreign countries faces several risks, such as perishability, bulky, diverse quality, and seasonality. Therefore, qualified management of risk barriers in the snake fruit supply chain system is needed, which is not only found in the distribution process but also in the production process and financial risks to maintain the quality of snake fruit. This study aims to identify potential risks, analyze the level of risk, and formulate risk mitigation measures in the snake fruit supply chain. The research method uses the intrinsic case study method and is analyzed using the House of Risk approach. The results showed that there were 32 risk events and 33 risk agents. Two of them are priority risks for mitigation, namely the risk of natural factors and demand fluctuations, which have led to 3 recommendations for mitigation actions, consisting of collaborating with related agencies and institutions, conducting intense communication among supply chain actors, and providing counselling and supervision of farmer-level snake fruit cultivation activities.